Meningkatkan Hasil Belajar Pendidikan Agama Katolik dengan Model Problem Based Learning (PBL) Fase B Kelas 4 SDN 14 Kuala Mandor B - Helena Pulo Rebong; Dikcy Aprianto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Education is an ongoing process aimed at developing human potential holistically, encompassing teaching, training, and experience. The Merdeka Curriculum allows schools, teachers, and students to adapt the learning process based on individual needs and potentials. In the context of Catholic Religious Education, its primary goal is to shape faith and character according to Catholic teachings. However, at SDN 14 Kuala Mandor B, the main challenge in Catholic Religious Education is the dominance of the lecture method, which results in low student participation. This affects the depth of understanding of the material taught. To address this issue, the implementation of Problem-Based Learning (PBL) can be an effective solution. PBL places students at the center of learning, encourages collaboration, and enhances active student engagement, thereby improving learning outcomes in line with the school's vision and mission.